The Role of Carotid Stenosis in a Prediction of Prognosis of Coronary Artery Disease - Paljoskovska Jordanova, Savetka; Kedev, Sasko; Petkoska Spirova, Danica; Stojanovska, Lily; Bosevski, Marijan (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/Walter de Gruyter GmbH/Walter de Gruyter GmbH, 2021)
Abstract Aims: The aim of this paper is to indicate if carotid stenosis is predictive for the prognosis of coronary artery disease. Method and materials: Our study is a prospective cohort study. 1031 patients with proven coronary artery disease (CAD) were recruited consecutively. Carotid ultrasound was used to assess IMT, plaque, or stenosis. They were followed for 24 months for adverse cardiovascular events. Selected demographic date such as smoking history, dyslipidemia, hypertension, laboratory values, and clinical data (associated diseases and risk) were collected from each patient. Total cardiovascular events and mortality rate were followed up for the study population. The results were collected prospectively and retrospectively. The study was organized as a clinical, cross-sectional study and comparative study. From the data collected with the clinical research, a file was formed in the statistical program with the help of which the data were statistically analyzed. From the methods of descriptive statistics, absolute frequencies, percentages, arithmetic mean, median, measures of variability, minimum, maximum, standard deviation and logistic regression models were used. Result: Of the total number of patients 1026 had arterial hypertension (HTA). Data on hyperlipidemia (HLP) had been reported in 895 patients. 1.023 patients had peripheral artery disease (PAB). 1031 patients were presented with multivessel coronary artery disease (CAD). There were 1,029 patients with diabetes mellitus (DM), while 1,013 patients had coronary artery by-pass (CABG), and 1,012 had stroke (CVI). Elevated systolic blood pressure was reported in 966 patients. 184 patients had elevated triglycerides and 187 had elevated cholesterol. 1,008 patients have had a history of myocardial infarction. Carotid artery stenosis (CAS) has been found in 1,009 patients, increased body mass index (BMI) in 270 patients. 1.031 patients were followed for 24 months. Cardiovascular events were reported in 54 patients (or 5.2%). Revascularization was performed in 28 (4.1%) patients, while 12 (1.8%) of patients died. Diabetes mellitus (OR 1.878 95% CI 0.491 7.184) and Carotid stenosis (OR 2.185 95% CI 0.731 6.53) were found to be predictive factors for future cardiovascular events. Conclusion: Due to our results carotid ultrasound may be a useful tool for risk stratification of coronary artery disease pts.